Analysis of Accessory Pudendal Artery Transection on Erections During Robot-Assisted Radical Prostatectomy - Williams, Stephen B. (J Endourol, 2017)
Purpose: To compare the recovery of erections and potency following the transection of accessory pudendal arteries (APAs) in men undergoing robot-assisted radical prostatectomy (RARP) compared with men with normal vascular anatomy. Materials and Methods: A total of 880 consecutive patients who underwent RARP from January 1, 2007 to December 31, 2014 were included with prospectively collected data in cross-sectional analysis. Erectile function (EF) was assessed preoperatively and postoperatively at 3, 6, 12, and 24 months using the International Index of Erectile Function (IIEF)-5, a percent erection fullness compared to preoperative status, and two Expanded Prostate Cancer Index (EPIC) questions: (1) are erections firm enough for penetration and (2) are they satisfactory? Results: Two hundred thirty-one (33.1%) men had APAs transected. There were no significant differences in baseline demographics or clinical characteristics in men with or without APAs transected. Multivariate analyses demonstrated that age (confidence interval [95% CI]: 0.94, 0.99) and baseline IIEF-5 (95% CI: 1.15, 1.26) strongly correlated with recovery of erections and potency. Transection of APAs was not a significant predictor of erectile dysfunction (ED). Conclusion: Good surgical technique dictates the preservation of APAs. However, when preservation is questioned, we found that APA transection had no measurable effect on recovery of erections or potency regardless of age, preoperative ED, or number of APAs transected.